Дослідження продуктивності провідних javascript-фреймворків - Дранченко, С. А. (ХНУРЕ, 2023)
This research focuses on the evaluation of the performance of leading JavaScript frameworks. The study delves into the analysis of various frameworks and their respective performance metrics, such as load time, rendering speed, file size, lines of code. The study aims to assist developers in selecting the most suitable JavaScript framework for their specific projects based on performance requirements.